Analisis Implementasi Program Guru Penggerak dalam Meningkatkan Kualitas Pembelajaran - Arinda Qomarin Almuqita; Ammar Muhammad Zaky; Muhammad Aufa Hafizh; Zulfaidan Zubeir Batubara (Indo-MathEdu Intellectuals Journal, 2026)
The Leading Teacher Program is a strategic effort to improve the quality of education by strengthening the role of teachers as learning leaders in educational units. This study aims to analyze the implementation of the Leading Teacher Program based on the POSC (Planning, Organizing, Staffing, and Controlling) theory and identify the implementation of work programs at the school level. The study used a descriptive qualitative approach with literature study and document review methods. Data collection techniques were carried out through analysis of policy documents, program reports, scientific articles, and various library sources relevant to the Leading Teacher Program. Data were analyzed using content analysis techniques through the stages of data reduction, categorization, interpretation, and drawing conclusions based on POSC management function indicators. The results of the study indicate that the planning function has been carried out through the preparation of learning programs and learning communities, but some programs have not fully aligned with school needs. In the organizational aspect, there is still limited collaboration between school members, while the staffing function is seen in the involvement of leading teachers as learning facilitators and agents of change. In addition, the supervisory function is still dominated by administrative evaluations and is not optimally oriented towards learning reflection.